Best men - Krevoy, Brad 1956-; Stabler, Steve; Jenkel, Brad; Ridpath, Deborah; Brown, Art Edler; Fraim, Tracy; Davis, Tamra 1962- (MGM Home Entertainment, 1997)
Hope's big mistake on her wedding day was sending the groomsmen to collect her jailbird fiance Jesse from prison. For on the way from the penitentiary, the best man, Billy, decides he needs a little cash infusion from the town bank...so he holds it up! But it's not long before all of the groomsmen are held up-when the cops surround the place! And since neither hell nor high water will stop Hope from having her day...she rushes in to join her fugitive wedding party, at the risk of spending her honeymoon - not to mention the rest of her life - behind bars!